2021
DOI: 10.1210/jendso/bvaa204
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Propylthiouracil in the First Trimester of Pregnancy and Birth Defects: A Study at a Single Institution

Abstract: Context Medical treatment of Graves disease during the first trimester has been the subject of controversy ever since treatment with an antithyroid drug during the first trimester was reported to possibly be associated with an increased risk of birth defects in newborns. Objective We investigated whether the incidence of birth defects among newborns born to mothers with Graves disease (GD) treated with propylthiouracil (PTU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In a second study from the same institution, Yoshihara et al reported an increased risk of birth defects in children of hypothyroid compared to euthyroid mothers (9.3% vs 3.8%, p = .03) although this association disappeared after correction for maternal age and treatment 33 . A recent study by the same authors reported no difference in FT4 or TSH concentrations in PTU‐treated mothers who delivered children with birth defects and those who delivered children without birth defects 20 . In a large Danish nationwide study, Andersen et al reported an increased risk of congenital anomalies in a subsection of children of overtly hypothyroid women compared to children of euthyroid mothers although a proportion of these mothers had received ATD treatment (OR, 1.91; 95% CI, 1.12–3.25) 12 …”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…In a second study from the same institution, Yoshihara et al reported an increased risk of birth defects in children of hypothyroid compared to euthyroid mothers (9.3% vs 3.8%, p = .03) although this association disappeared after correction for maternal age and treatment 33 . A recent study by the same authors reported no difference in FT4 or TSH concentrations in PTU‐treated mothers who delivered children with birth defects and those who delivered children without birth defects 20 . In a large Danish nationwide study, Andersen et al reported an increased risk of congenital anomalies in a subsection of children of overtly hypothyroid women compared to children of euthyroid mothers although a proportion of these mothers had received ATD treatment (OR, 1.91; 95% CI, 1.12–3.25) 12 …”
Section: Resultsmentioning
confidence: 94%
“…Three studies evaluated anomaly risk in relation to ATD dose but were not comparable by meta‐analysis. The two hospital studies by Momotani and Yoshihara showed no association between ATD dose and birth defects 14,20 . In contrast, a large Korean nationwide database study by Seo et al reported that children of women who received a high cumulative dose of MMI had an increased anomaly risk compared to those who received lower doses (495 vs. <126 mg, OR, 1.87; 95% CI, 1.06–3.30).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations